Coating film protective coating materials and coating compositions

CN117321154BActive Publication Date: 2026-10-09NITTO DENKO CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202280035648.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-04-26
Filing Date
2022-05-13
Publication Date
2026-10-09
Estimated Expiration
2042-05-13

AI Technical Summary

Benefits of technology

[0008] The problem the invention aims to solve

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117321154B_ABST
    Figure CN117321154B_ABST
Patent Text Reader

Abstract

A coating film protective coating material formed from a liquid coating composition is provided. The above coating composition contains a polymer (A) as a base polymer, which is a polymer of a monomer component containing an acrylic monomer. The above polymer (A) has an SP value of 9.8 (cal / cm 3 ) 1 / 2 The above, and a glass transition temperature calculated based on the composition of the monomer component constituting the polymer (A) is 0°C or lower.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to protective coating materials and coating compositions for forming protective coating materials.

[0002] This application claims priority based on Japanese Patent Application No. 2021-082914, filed on May 17, 2021; Japanese Patent Application No. 2022-024082, filed on February 18, 2022; and Japanese Patent Application No. 2022-072650, filed on April 26, 2022, the entire contents of which are incorporated herein by reference. Background Technology

[0003] For the purpose of preventing damage to the coating during the transportation, storage, maintenance, and application of coated articles (e.g., painted automobiles, their components, or coated steel sheets and other metal plates, their formed articles, etc.), a technique for protecting the coating by attaching a protective sheet is known. The protective sheet used for this purpose is generally constructed as follows: it is a single-sided adhesive sheet with a substrate having an adhesive (also called a pressure-sensitive adhesive, hereinafter the same) layer on one side of a sheet-like substrate (supporting substrate), and is attached to the object to be protected by means of this adhesive, thereby achieving the protective purpose. The protective sheet, having completed its protective function, is then removed (peeled off) from the object. Patent Document 1 is cited as a technical document concerning protective sheets for coatings.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2011-111552

[0007] Patent Document 2: Japanese Patent Application Publication No. 2004-224874 Summary of the Invention

[0008] The problem the invention aims to solve

[0009] However, for objects with non-planar shapes (especially complex three-dimensional objects like automobile exterior panels), it is difficult to efficiently apply protective coatings to them. If the protective coating is not applied properly, for example, if it is applied with wrinkles, these wrinkles can be blown in during storage or transport of the object after application, sometimes causing the protective coating to peel off and failing to achieve its intended protective purpose.

[0010] On the other hand, it has been proposed to directly apply a liquid composition for forming a protective film onto a coating of the object to be protected, and then dry the liquid composition on the coating to form a protective film. Patent Document 2 is cited as a relevant document for this technology. However, unlike the aforementioned protective film, the protective film formed by the liquid composition does not have a substrate, and therefore often suffers from insufficient peelability when removed from the coating after the protective effect has been achieved. Furthermore, the protective film (coating protective coating material) formed by the liquid composition, like conventional protective films, requires the property of not leaving any traces of the protective film on the coating after removal, i.e., anti-trace adhesion, but improving peelability while preventing trace adhesion is particularly difficult.

[0011] Therefore, an object of the present invention is to provide a protective coating material formed from a liquid coating composition, which exhibits good peelability and anti-marking adhesion when removed from a coating film. Another related object is to provide a coating composition suitable for forming the aforementioned protective coating material and a method for forming the aforementioned protective coating material.

[0012] Solution for solving the problem

[0013] According to this specification, a protective coating material (hereinafter sometimes simply referred to as "coating material") formed from a liquid coating composition is provided. The coating composition comprises a polymer (A) as a base polymer, said polymer (A) being a polymer containing an acrylic monomer component. The SP value of said polymer (A) is 9.8 (cal / cm³). 3 ) 1 / 2 That's all. Furthermore, the glass transition temperature (hereinafter also referred to as "calculated Tg") of the polymer (A) calculated based on the composition of the monomer components is below 0°C. Using such a coating material, a good balance can be achieved between excellent peelability and good anti-marking adhesion of the self-coated film.

[0014] In some embodiments of the techniques disclosed herein (including coating materials, coating compositions, coating protection methods, etc. The same applies hereinafter), the acid value of the polymer (A) is 15 mg KOH / g or less. By limiting the acid value of the polymer (A) to a specified level, it is easy to suppress the peel strength when the coating material formed on the coating film is peeled off from the coating film. This is preferred from the viewpoint of improving peelability and peel workability.

[0015] The protective coating material disclosed herein preferably has a storage modulus (hereinafter sometimes referred to as "G'(70)") of 0.40 MPa or higher at 70°C. Coating materials with such a G'(70) exhibit good self-coating peelability.

[0016] In some embodiments, the monomer component preferably includes a nitrogen-containing monomer. That is, the polymer (A) is preferably a polymer containing a nitrogen-containing monomer component. Using this monomer component, it is easy to obtain a polymer (A) that has both a calculated Tg value below a specified value and a SP value above a specified value.

[0017] In some embodiments, the Tg of the polymer (A) calculated based on the composition of the monomer components is -20°C or higher. It is preferable from the viewpoint of improving the peelability of the self-coating film if the calculated Tg of polymer (A) is not too low.

[0018] In some embodiments, the monomeric components constituting the polymer (A) may be a composition comprising an alkyl (meth)acrylate having an alkyl group having 1 to 3 carbon atoms at the ester terminus, and a carboxyl-containing monomer. Using a polymer (A) composed of such monomeric components, it is easy to obtain a coating material and a coating composition suitable for forming such a coating material that achieve a good balance between anti-marking adhesion, peeling properties, and peeling performance.

[0019] Furthermore, according to this specification, coating compositions for forming any of the protective coating materials disclosed herein are provided. The protective coating materials disclosed herein can preferably be formed by using the above-described coating compositions, for example, by applying the coating composition onto a coating film and drying it.

[0020] In some embodiments of the technology disclosed herein, the coating composition is preferably a composition in which the polymer (A) is dispersed in an aqueous emulsion form in an aqueous solvent. Such an aqueous emulsion-type coating composition is preferred from an environmental hygiene point of view, as it is suitable for suppressing, for example, the amount and release of organic solvents.

[0021] According to this specification, a coating protection method is provided, comprising: preparing any coating composition disclosed herein; applying the coating composition onto the coating film of a protected object having a coating film; and drying the coating composition to form a coating protective coating material that temporarily protects the coating film. Using the above coating protection method, the coating film can be properly protected using the coating material. Furthermore, using the coating material, a good balance can be achieved between good peelability and good anti-marking adhesion of the self-coated film.

[0022] In some preferred embodiments, the coating composition is applied using a slit mold. By drying the coating composition applied through the slit mold, a protective coating material can be efficiently formed on the coating film.

[0023] It should be noted that a suitable combination of the elements described in this specification may also be included in the claims for patent protection in this application. Attached Figure Description

[0024] Figure 1 A cross-sectional view is shown schematically as an example of an object protected by the coating material of the present invention.

[0025] Figure 2 A block diagram illustrating one embodiment of the coating protection method of the present invention. Detailed Implementation

[0026] The following describes suitable embodiments of the present invention. For matters necessary for the implementation of the present invention other than those specifically described in this specification, those skilled in the art can understand them based on the teachings regarding the implementation of the invention described in this specification and common technical knowledge at the time of application. The present invention can be implemented based on the disclosures in this specification and common technical knowledge in the field.

[0027] It should be noted that in the following figures, components or parts that perform the same function are sometimes labeled with the same symbols, and repeated descriptions are sometimes omitted or simplified. Furthermore, the embodiments described in the figures are schematic for the purpose of clearly illustrating the invention and may not accurately represent the dimensions or scale of the actual product provided.

[0028] In this specification, "acrylic monomer" broadly refers to monomers having at least one (meth)acryloyl group in one molecule (hereinafter also referred to as "(meth)acryloyl-containing monomers") and the concept of (meth)acrylonitrile. Furthermore, in this specification, "(meth)acryloyl" broadly refers to both acryloyl and methacryloyl groups. Similarly, "(meth)acrylate" broadly refers to both acrylates and methacrylates, "(meth)acrylic acid" broadly refers to both acrylic acid and methacrylic acid, and "(meth)acrylonitrile" broadly refers to both acrylonitrile and methacrylonitrile.

[0029] <Polymer (A)>

[0030] The protective coating material disclosed herein is formed from a coating composition comprising a polymer (A) as a base polymer. Here, "base polymer" refers to a component comprising more than 50% by weight (typically 70% or more, for example 90% or more, possibly 95% or more, or possibly 100% by weight) of the polymer contained in the coating composition. The base polymer in the protective coating material has the same meaning. The polymer (A) is a polymer comprising an acrylic monomer component. Therefore, the polymer (A) is a polymer comprising monomer units derived from acrylic monomers.

[0031] The polymer (A) described above has a strength of 9.8 or higher (unit [(cal / cm)]). 3 )1 / 2 The SP value of the polymer (A) is as follows. A polymer (A) having an SP value of 9.8 or higher may have an SP value that differs significantly (typically even more) from the SP value of the coating film being protected. The aforementioned coating film may be, for example, a urethane-based coating film formed by the reaction of a polyol (e.g., an acrylic polyol) with a polyisocyanate, or a coating film formed by an acid-epoxy crosslinking acrylic coating. By making the SP value of the polymer (A) significantly different from the SP value of the coating film, there is a tendency to reduce the interaction between the coating material containing the polymer (A) and the coating film. This is advantageous from the viewpoints of suppressing poor peeling due to excessively high peel strength of the coating material from the coating film, increasing the burden of peeling operations, and suppressing coating film deformation (trace adhesion) caused by material movement between the coating film and the coating material. In some embodiments, the SP value of the polymer (A) is preferably 9.9 or higher, more preferably 10.0 or higher, may be 10.5 or higher, may be 10.8 or higher, may be 11.2 or higher, or may be 11.5 or higher. There is no particular upper limit to the SP value of polymer (A). From the viewpoint of easily balancing the calculated Tg below the specified value and easily forming a coating material with a good balance of properties, in some cases, it is appropriate for the SP value of polymer (A) to be approximately 14.0 or less, but it can be 13.5 or less, less than 12.5, less than 12.0, less than 12.0, or even less than 11.5.

[0032] Here, in this specification, the SP value refers to the solubility parameter calculated from the basic structure of the compound using the method proposed by Fedors. The SP value of polymer (A) can be adjusted by selecting the composition of the monomer components constituting polymer (A), specifically by selecting the types and proportions of monomers included in the aforementioned monomer components.

[0033] In some methods, it is appropriate, preferably 0.5 or more, more preferably 0.7 or more, and even more preferably 1.0 or more, for the polymer (A) to have a higher SP value than the coating film to be protected. By combining the polymer (A) with such a difference in SP value with the coating film to be protected, it is easy and suitable to achieve good peelability and good anti-marking adhesion of the coating material containing the polymer (A).

[0034] The glass transition temperature (calculated Tg) of the polymer (A) described above, calculated based on the composition of the monomer components constituting the polymer (A), is below 0°C. Coating materials containing a polymer (A) designed with a calculated Tg of 0°C or lower as the base polymer exhibit good anti-marking adhesion properties. By using a polymer (A) designed to satisfy the aforementioned SP value and have a calculated Tg below 0°C as the base polymer, coating materials with good peelability upon removal from the coating film and good anti-marking adhesion properties can be suitably achieved. A calculated Tg of below 0°C for polymer (A) is also preferred from the viewpoint of easily achieving coating materials with a moderately high elongation at break, as described later. The lower limit of the calculated Tg of polymer (A) is not particularly limited; for example, it can be above -50°C. In some approaches, from the viewpoint of peeling workability (e.g., suppressing poor peeling caused by defects or breakage of the coating material) when peeling the coating material from the film at temperatures near room temperature (e.g., around 15–30°C), a calculated Tg of -40°C or higher for the polymer (A) is appropriate, -35°C or higher is advantageous, -20°C or higher is preferred, and it can be -15°C or higher, or -13°C or higher. On the other hand, from the viewpoint of easily improving anti-marking adhesion, the calculated Tg of the polymer (A) can be, for example, -1.0°C or lower, -5.0°C or lower, -8.0°C or lower, or -10.0°C or lower. Lowering the calculated Tg of the polymer (A) is preferred from the viewpoint of peeling workability when peeling the coating material from the film in low-temperature environments such as outdoor winters, and is also advantageous from the viewpoint of suppressing the phenomenon of cracking in the coating material due to the difference in the coefficient of linear expansion between the coated object and the protected object when exposed to temperature changes. The Tg of polymer (A) can be adjusted by selecting the composition of the monomer components that constitute polymer (A), specifically by selecting the types and proportions of monomers included in the monomer components.

[0035] Here, in this specification, the calculated Tg of a polymer refers to the Tg obtained using the Fox formula based on the composition of the monomer components used in the synthesis of the polymer. The Fox formula, as shown below, is a relationship between the Tg of the copolymer and the glass transition temperature Tgi of the homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer.

[0036] 1 / Tg=Σ(Wi / Tgi)

[0037] It should be noted that in the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight percentage of monomer i in the copolymer (weight-based copolymerization ratio), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K).

[0038] The glass transition temperature of the homopolymer used in calculating Tg is the value recorded in known sources. For example, for the monomers listed below, the following values ​​are used as the glass transition temperature of the homopolymer of that monomer.

[0039]

[0040] Regarding the glass transition temperature (Tg) of homopolymers of monomers other than those exemplified above, the values ​​described in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) are used. Where the Tg of the homopolymer is not described in publicly available materials, the values ​​obtained by the measurement method described in Japanese Patent Application Publication No. 2007-51271 are used. Specifically, in a reactor equipped with a thermometer, stirrer, nitrogen inlet pipe, and reflux condenser, 100 parts by weight of monomer, 0.2 parts by weight of azobisisobutyronitrile (AIB), and 200 parts by weight of ethyl acetate as the polymerization solvent are added, and the mixture is stirred for 1 hour while nitrogen is flowing through it. After removing oxygen from the polymerization system, the temperature is raised to 63°C and the reaction is carried out for 10 hours. Then, the mixture is cooled to room temperature to obtain a homopolymer solution with a non-volatile component concentration of 33% by weight. Next, this homopolymer solution is cast onto a release liner, dried, and a test sample (sheet-shaped homopolymer) with a thickness of approximately 2 mm is prepared. The test sample was punched into a disc shape with a diameter of 7.9 mm and clamped with parallel plates. The viscoelasticity was measured in shear mode using a viscoelastic testing machine (manufactured by TA Instruments Japan Inc., model name "ARES") while a shear strain of 1 Hz was applied. The temperature range was -70 to 150 °C and the temperature was increased at a rate of 5 °C / min. The peak temperature of tanδ was taken as the Tg of the homopolymer.

[0041] The polymer (A) disclosed herein is a polymer comprising one or more acrylic monomers. The proportion of acrylic monomers in the aforementioned monomer composition may be, for example, 5 mol% or more, 10 mol% or more, preferably 15 mol% or more, 25 mol% or more, 35 mol% or more, 45 mol% or more, more than 50 mol%, or more than 70 mol%. In some preferred embodiments, the proportion of acrylic monomers in the aforementioned monomer composition may be 85 mol% or more, 90 mol% or more, 95 mol% or more, or 100 mol%. Furthermore, in some embodiments, the proportion of acrylic monomers in the aforementioned monomer composition may be 50 mol% or less, 40 mol% or less, or 30 mol% or less.

[0042] In some embodiments, the monomeric component constituting polymer (A) includes at least a (meth)acryloyl monomer as an acrylic monomer. The (meth)acryloyl monomer can be used alone or in combination of two or more. The proportion of the (meth)acryloyl monomer in the monomeric component can be, for example, 5 mol% or more, 10 mol% or more is suitable, preferably 15 mol% or more, more preferably 20 mol% or more, 30 mol% or more, 40 mol% or more, 45 mol% or more, 50 mol% or more, 55 mol% or more, or 60 mol% or more. Alternatively, all (i.e., 100 mol%) of the monomeric component can be a (meth)acryloyl monomer. From the viewpoint of easily achieving a calculated Tg below the specified value and easily forming a coating material with a good balance of properties, in some embodiments, the proportion of the (meth)acryloyl monomer in the monomeric component is preferably 95 mol% or less, more preferably 90 mol% or less, can be 85 mol% or less, can be 80 mol% or less, can be 75 mol% or less, or can be 70 mol% or less. The techniques disclosed herein can also be implemented in a manner in which the proportion of (meth)acryloyl monomer in the monomer component is less than 65 mol%, less than 55 mol%, less than 45 mol%, or less than 35 mol%.

[0043] The monomer components constituting the polymer (A) preferably include at least an alkyl methacrylate as the (meth)acryloyl-containing monomer. The type and amount of alkyl methacrylate can be selected to help adjust the storage modulus, tensile properties, and SP value (described later). Alkyl methacrylates can be used alone or in combination of two or more.

[0044] As an alkyl methacrylate, for example, a compound represented by the following formula (1) may be suitable.

[0045] CH2=C(R 1 COOR 2 (1)

[0046] Here, R in equation (1) above... 1 R is a hydrogen atom or a methyl group. In formula (1) above, R... 2 It is a chain alkyl group having 1 to 20 carbon atoms. Hereinafter, this range of carbon atoms is sometimes expressed as "C". 1-20 The aforementioned chain alkyl groups can be straight-chain or branched.

[0047] As R 2 C 1-20 Alkyl (meth)acrylates ((meth)acrylate C) 1-20Specific examples of alkyl esters are not particularly limited, but can include methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, isoamyl methacrylate, hexyl methacrylate, heptyl methacrylate, 2-ethylhexyl methacrylate, octyl methacrylate, isooctyl methacrylate, nonyl methacrylate, isononyl methacrylate, decyl methacrylate, isodecyl methacrylate, undecyl methacrylate, dodecyl methacrylate, tridecyl methacrylate, tetradecyl methacrylate, pentadecyl methacrylate, hexadecyl methacrylate, heptadecanyl methacrylate, octadecyl methacrylate, nonadecanyl methacrylate, eicosyl methacrylate, etc.

[0048] Of these, it is preferred to use at least (meth)acrylic acid C. 4-20 Alkyl ester (preferably (meth)acrylic acid C) 4-14 Alkyl esters), from the perspective that they can help reduce the calculated Tg of polymer (A), are more preferably made by using at least acrylic acid C. 4-9 Alkyl esters. For example, the monomeric components mentioned above preferably include one or both of n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA), more preferably at least BA.

[0049] The monomer component (meth)acrylic acid C in polymer (A) 1-20 The proportion of alkyl esters can be, for example, 5 mol% or more, 10 mol% or more, preferably 15 mol% or more, 25 mol% or more, 35 mol% or more, 45 mol% or more, 55 mol% or more, or 60 mol% or more. Furthermore, from the viewpoint of easily obtaining polymers (A) that satisfy the above-mentioned SP values ​​and calculated Tg values ​​below the specified limits, the monomer component (meth)acrylic acid C... 1-20 The proportion of alkyl esters is suitable at 95 mol% or less, preferably 90 mol% or less, but can be 85 mol% or less, 75 mol% or less, or 65 mol% or less. The techniques disclosed herein can also be used with (meth)acrylic acid C in the monomer component. 1-20 The alkyl ester is implemented in a manner where the proportion is less than 60 mol%, less than 50 mol%, less than 40 mol%, or less than 30 mol%.

[0050] The monomer components constituting polymer (A) include acrylic acid C.4-9 In the alkyl ester formulation, acrylic acid C is a monomer component. 4-9 The proportion of alkyl esters can be, for example, 5 mol% or more, or 10 mol% or more. From the viewpoint of easily obtaining a lower calculated Tg, it is preferable to be 15 mol% or more, or 25 mol% or more, or 35 mol% or more, or 40 mol% or more, or 45 mol% or more. On the other hand, from the viewpoint of easily obtaining a polymer (A) with a specified or higher SP value, the acrylic acid C in the monomer component... 4-9 The proportion of alkyl esters is suitable at 80 mol% or less, preferably 70 mol% or less, and can be 65 mol% or less, or 55 mol% or less. The techniques disclosed herein can also be used with acrylic acid C in the monomer composition. 4-9 The alkyl ester is implemented in a manner where the proportion is less than 50 mol%, less than 40 mol%, less than 30 mol%, less than 25 mol%, or less than 20 mol%.

[0051] The monomer components constituting polymer (A) can also include alkyl (meth)acrylates and monomers other than alkyl (meth)acrylates. Examples of monomers other than alkyl (meth)acrylates include carboxyl-containing monomers, hydroxyl (OH)-containing monomers, cyano-containing monomers, amide-containing monomers, amino-containing monomers, monomers with nitrogen-containing rings, anhydride-containing monomers, epoxy-containing monomers, ketone-containing monomers, and alkoxysilyl-containing monomers, among other functionalized monomers. By appropriately using functionalized monomers, the cohesive strength of polymer (A) can be improved. Functionalized monomers can also help adjust the storage modulus, tensile properties, and SP value (described later).

[0052] Examples of carboxyl-containing monomers include acrylic acid (AA), methacrylic acid (MAA), carboxyethyl methacrylate, carboxypentyl methacrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid. Among these, AA and MAA are preferred.

[0053] Examples of hydroxyl-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and other hydroxyalkyl (meth)acrylates; polypropylene glycol mono(meth)acrylate, etc. Preferred hydroxyl-containing monomers include linear (meth)acrylates with an alkyl group having 2 to 4 carbon atoms.

[0054] Examples of cyano-containing monomers include acrylonitrile, methacrylonitrile, and 2-cyanoethyl (meth)acrylate. Among these, acrylonitrile and methacrylonitrile are preferred, with acrylonitrile being the most preferred.

[0055] Examples of amide-containing monomers include (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-butyl (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, and diacetone (meth)acrylamide.

[0056] Examples of amino-containing monomers include aminoethyl methacrylate, N,N-dimethylaminoethyl methacrylate, and tert-butylaminoethyl methacrylate.

[0057] Examples of monomers having a nitrogen-containing ring include N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazolium, N-vinyloxazole, N-vinylmorpholine, N-vinylcaprolactam, and N-(meth)acryloylmorpholine, which are monomers with polymerizable functional groups bonded to a nitrogen-containing ring. Other examples include monomers containing a maleimide ring, such as N-isopropylmaleimide and N-cyclohexylmaleimide.

[0058] As an example of a monomer containing an isocyanate group, 2-(meth)acryloyloxyethyl isocyanate can be cited.

[0059] Examples of monomers containing anhydride groups include maleic anhydride and itaconic anhydride.

[0060] Examples of ketone-containing monomers include diacetone (meth)acrylate, vinyl methyl ketone, vinyl ethyl ketone, allyl acetoacetate, and vinyl acetoacetate.

[0061] Examples of monomers with epoxy groups include glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, and allyl glycidyl ether.

[0062] Examples of alkoxysilyl monomers include 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyltriethoxysilane, 3-(meth)acryloyloxypropylmethyldimethoxysilane, and 3-(meth)acryloyloxypropylmethyldiethoxysilane.

[0063] For purposes such as improving cohesion, the monomer components constituting polymer (A) may also include other copolymer components besides the monomers mentioned above. Examples of other copolymer components include vinyl ester monomers such as vinyl acetate (VAc), vinyl propionate, and vinyl laurate; aromatic vinyl compounds such as styrene, substituted styrene (α-methylstyrene, etc.), and vinyltoluene; cycloalkyl methacrylates such as cyclohexyl methacrylate, cyclopentyl methacrylate, and isobornyl methacrylate; aryl methacrylates (e.g., phenyl methacrylate), aryloxyalkyl methacrylates (e.g., phenoxyethyl methacrylate), and arylalkyl methacrylates (e.g., benzyl methacrylate). (Meth)acrylates containing aromatic rings; olefin monomers such as ethylene, propylene, isoprene, butadiene, and isobutylene; monomers containing chlorine atoms such as vinyl chloride and vinylidene chloride; alkoxy monomers such as methoxyethyl methacrylate, ethoxyethyl methacrylate, and ethyl carbitol (meth)acrylate; vinyl ether monomers such as methyl vinyl ether and ethyl vinyl ether; polyfunctional monomers such as 1,6-hexanediol di(meth)acrylate and trimethylolpropane tri(meth)acrylate, having two or more (e.g., three or more) polymerizable functional groups (e.g., (meth)acryloyl) in one molecule; etc.

[0064] In some embodiments, the monomeric components constituting polymer (A) include nitrogen-containing monomers. Examples of nitrogen-containing monomers include monomers that are at least one of the aforementioned cyano-containing monomers, amide-containing monomers, amino-containing monomers, and monomers having a nitrogen-containing ring. One nitrogen-containing monomer may be used alone or in combination of two or more. Preferably, the monomeric components comprise alkyl (meth)acrylates and nitrogen-containing monomers, and more preferably, C-acrylates. 4-9 Alkyl esters and nitrogen-containing monomers. Nitrogen-containing monomers, by including a nitrogen-containing structural moiety, tend to exhibit higher SP values ​​(e.g., higher SP values ​​than (meth)acrylate alkyl esters). By appropriately using nitrogen-containing monomers, polymers (A) with SP values ​​exceeding a specified value can be readily obtained. Furthermore, nitrogen-containing monomers generally tend to have high Tg values ​​in homopolymers. When nitrogen-containing monomers are used as monomeric components constituting polymer (A), the calculated Tg of polymer (A) tends to increase. In this case, by appropriately combining the nitrogen-containing monomer with acrylic acid C... 4-9 The use of alkyl esters in combination can appropriately achieve polymers (A) that balance above-specified SP values ​​and below-specified Tg values.

[0065] In a monomer composition comprising polymer (A) that includes nitrogen-containing monomers, the proportion of nitrogen-containing monomers in this monomer composition can be set in a manner that yields the desired performance effect. In some embodiments, the proportion of nitrogen-containing monomers in the monomer composition can be, for example, 1 mol% or more, 5 mol% or more is suitable, preferably 10 mol% or more, more preferably 15 mol% or more, 20 mol% or more, 25 mol% or more, 30 mol% or more, or 35 mol% or more. On the other hand, from the viewpoint of easily achieving a calculated Tg of polymer (A) below a specified value, the proportion of nitrogen-containing monomers in the monomer composition can be 70 mol% or less, preferably 65 mol% or less, 60 mol% or less, 55 mol% or less, 50 mol% or less, 45 mol% or less, or 40 mol% or less.

[0066] In some preferred embodiments, the monomer component constituting polymer (A) includes at least acrylonitrile as the aforementioned nitrogen-containing monomer. By including acrylonitrile in the monomer component, it is easy to achieve a coating material and a coating composition capable of forming such a coating material that achieve a good balance between good peelability and good anti-marking adhesion. The proportion of acrylonitrile in the nitrogen-containing monomer included in the monomer component can be, for example, 25 mol% or more, 50 mol% or more, 70 mol% or more, 85 mol% or more, 95 mol% or more, or 100 mol%.

[0067] In a monomeric component comprising polymer (A), the proportion of acrylonitrile in the monomeric component can be, for example, 1 mol% or more, 5 mol% or more, preferably 10 mol% or more, more preferably 15 mol% or more, 20 mol% or more, 25 mol% or more, 30 mol% or more, or 35 mol% or more. On the other hand, from the viewpoint of easily achieving a calculated Tg of polymer (A) below a specified value, the proportion of acrylonitrile in the monomeric component can be 70 mol% or less, preferably 65 mol% or less, 60 mol% or less, 55 mol% or less, 50 mol% or less, 45 mol% or less, or 40 mol% or less.

[0068] The acid value of polymer (A) is not particularly limited, and may be, for example, below 60 mg KOH / g. In some embodiments, from the viewpoint of suppressing the peel strength of the self-coated film, an acid value of polymer (A) of 20.0 mg KOH / g or less is advantageous, preferably below 15.0 mg KOH / g, more preferably below 12.0 mg KOH / g, below 11.0 mg KOH / g, or below 10.0 mg KOH / g. The techniques disclosed herein can also be implemented with an acid value of polymer (A) of 8.0 mg KOH / g or less, 6.0 mg KOH / g or less, 3.0 mg KOH / g or less, or 1.0 mg KOH / g or less. The acid value of polymer (A) may be 0 mg KOH / g or higher. In some approaches, from the viewpoint of improving the strength of the coating material (e.g., fracture strength), the acid value of polymer (A) can be, for example, 1.0 mg KOH / g or higher, 2.0 mg KOH / g or higher, 4.0 mg KOH / g or higher, or 7.0 mg KOH / g or higher. Improving the strength of the coating material is advantageous from the viewpoint of improving peelability (e.g., preventing breakage or damage during peeling).

[0069] The acid value of polymer (A) was determined based on the potentiometric titration method specified in JIS K0070:1992. Specifically, the acid value determination can be performed using the method described in the examples below. For the polymer (A) contained in the coating material, a mixture obtained by adding chloroform to the coating material was allowed to stand for 12 hours. The mixture was then filtered, and a substance with a weight-average molecular weight of 10,000 or more (determined by GPC) was used as the sample. For the acid value of polymer (A) contained in the coating composition, after drying the coating composition at 80°C for 3 minutes to form a film (coating material) with a thickness of approximately 100 μm, the same procedure as for the acid value determination of polymer (A) contained in the coating material was followed, and the resulting substance was used as the sample for determination. The acid value of polymer (A) contained in the aqueous emulsion of polymer (A) described below was determined using a substance obtained in the same procedure as for the acid value determination of polymer (A) contained in the coating composition.

[0070] In some embodiments of the technology disclosed herein, the monomeric components constituting the polymer (A) include monomers (m) whose homopolymer Tg is above 90°C. T The Tg of the monomers (m) and homopolymers is below -30℃. L Here, the aforementioned monomer (m) TThe polymer (A) can contain nitrogen-containing monomers with a Tg of 90°C or higher. Acrylonitrile (Tg of homopolymer: 97°C) is an example of a nitrogen-containing monomer with a Tg of 90°C or higher in a homopolymer. Therefore, the polymer (A) in this manner can contain monomers (m... L ) and monomers containing at least a nitrogen-containing monomer (e.g., acrylonitrile) (m T (and optionally, polymers containing other monomer components.) It should be noted that the Tg of the homopolymers of each monomer is the glass transition temperature of the homopolymer used in the calculation of the Tg above, using the value recorded in known sources. If the Tg of the homopolymer is not recorded in known sources, the value obtained by the measurement method described in Japanese Patent Application Publication No. 2007-51271 is used.

[0071] monomer (m) L This can help to moderately reduce the calculated Tg of polymer (A), thereby improving the anti-marking adhesion of coating materials containing polymer (A). Reducing the calculated Tg of polymer (A) is also advantageous from the viewpoint of improving the low-temperature properties of the coating material (e.g., suppressing crack initiation at low temperatures, suppressing cracking and breakage during self-peeling at low temperatures). As a monomer (m... L Monomers with a Tg below -30°C can be used, for example, selected from the various monomers mentioned above, but not limited to these. Monomer (m L It can be used alone or in combination of two or more. It can be used as a single unit (m) L Non-limiting examples of monomers used include n-butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), isooctyl acrylate, isononyl acrylate, isopentyl acrylate, 4-hydroxybutyl acrylate (4HBA), methoxyethyl acrylate, ethyl carbitol acrylate, ethoxy-diethylene glycol acrylate, etc.

[0072] As a monomer (m L The lower limit of the Tg of the homopolymers of the monomers used is not particularly limited; for example, it can be above -100°C, above -90°C, or above -80°C. In some methods, monomers with a Tg of -60°C to -40°C are preferably used as monomers (m). L Monomer (m) L In the homopolymer, the proportion of monomers with a Tg range of -60°C to -40°C can be, for example, 50 mol% or more, 75 mol% or more, 85 mol% or more, 95 mol% or more, or 100 mol%.

[0073] monomer (m) TThis can help improve the cohesiveness and high-temperature properties of coating materials (such as suppressing the decrease in storage modulus in high-temperature regions and peelability at high temperatures). Monomer (m T (One type can be used alone, or two or more types can be used in combination.) Monomer (m) T It can contain only one type of nitrogen-containing monomer, or a combination of two or more nitrogen-containing monomers, or a combination of one or more nitrogen-containing monomers with other monomers whose Tg of the homopolymer is above 90℃ (i.e., monomers that are not nitrogen-containing monomers; hereinafter also referred to as "monomers without nitrogen atoms"). As a monomer (m... T Acrylonitrile can be used alone, or in combination with a nitrogen-free monomer of homopolymer with a Tg of 90°C or higher, or in combination with a nitrogen-containing monomer of homopolymer with a Tg of 90°C or higher (except for acrylonitrile). The nitrogen-free monomer of homopolymer with a Tg of 90°C or higher can be suitably selected from, for example, the monomers mentioned above, but is not limited to these. The nitrogen-free monomers mentioned above can be used alone or in combination of two or more with a nitrogen-containing monomer of homopolymer with a Tg of 90°C or higher (e.g., acrylonitrile). As a monomer (m... T There is no particular limit to the upper limit of the Tg of the homopolymer of each monomer used, for example, it can be below 250°C, below 200°C or below 150°C.

[0074] Can be used as a monomer (m) T Non-limiting examples of monomers that do not contain nitrogen atoms include acrylic acid, methacrylic acid, methyl methacrylate, methacrylonitrile, acryloylmorpholine, acrylamide, isobornyl acrylate, isobornyl methacrylate, dicyclopentyl acrylate, dicyclopentyl methacrylate, adamantyl acrylate, tert-butyl methacrylate, etc. Suitable examples include acrylic acid (AA) and methyl methacrylate (MMA).

[0075] monomer (m) T The content of nitrogen-containing monomers in the membrane can be, for example, 35 mol% or more, and from the viewpoint of easily achieving suitable membrane properties, 50 mol% or more is appropriate, and preferably 60 mol% or more. In some embodiments, the monomer (m T The content of nitrogen-containing monomers in the () can exceed 70 mol%, 80 mol%, 90 mol%, 93 mol%, or even 100 mol%. Furthermore, in some methods, the monomer (m T The content of nitrogen-containing monomers in the ) can be less than 85 mol%, less than 75 mol%, less than 70 mol%, or less than 65 mol%.

[0076] In some methods, monomers (m T The nitrogen-containing monomer contained in the ) includes at least acrylonitrile. In this manner, the monomer (m T The proportion of acrylonitrile in the nitrogen-containing monomer contained in the product can be, for example, 25 mol% or more, 50 mol% or more, 70 mol% or more, 85 mol% or more, 95 mol% or more, or 100 mol%.

[0077] In monomer (m T In a manner that includes acrylonitrile, the monomer (m) T The acrylonitrile content in the membrane can be, for example, 35 mol% or more, and from the viewpoint of easily achieving suitable membrane properties, 50 mol% or more is appropriate, and preferably 60 mol% or more. In some embodiments, the monomer (m T The acrylonitrile content in the product can exceed 70 mol%, 80 mol%, 90 mol%, 93 mol%, or even 100 mol%. Furthermore, in some formulations, the monomer (m... T The acrylonitrile content in the product can be less than 85 mol%, less than 75 mol%, less than 70 mol%, or less than 65 mol%.

[0078] The monomer components constituting polymer (A) include monomers (m T ) and monomers (m L In the above-mentioned monomer components, the proportion of nitrogen-containing monomers with a Tg of 90°C or higher in the homopolymer can be, for example, 20 mol% or more. From the viewpoint of easily achieving suitable film properties, 25 mol% or more (e.g., 28 mol% or more) is appropriate, preferably 30 mol% or more, 35 mol% or more, or 40 mol% or more. The technology disclosed herein can preferably be implemented in a manner where the proportion of nitrogen-containing monomers with a Tg of 90°C or higher in the homopolymer constituting polymer (A) is greater than 50 mol%. Furthermore, from the viewpoint of the flexibility of the coating material, the proportion of nitrogen-containing monomers with a Tg of 90°C or higher in the homopolymer of the above-mentioned monomer components is appropriate to be 60 mol% or less, preferably less than 60 mol%. In some embodiments, the proportion of nitrogen-containing monomers with a Tg of 90°C or higher in the homopolymer can be 57 mol% or less, or 56 mol% or less. The technology disclosed herein can also be implemented with the proportion of nitrogen-containing monomers in the homopolymer having a Tg of 90°C or higher being 53 mol% or less, 50 mol% or less, or even 40 mol% or less.

[0079] The monomer components constituting polymer (A) include monomers (m T ) and monomers (m LIn the manner described herein, the acrylonitrile content in the total monomer component can be, for example, 20 mol% or more. From the viewpoint of easily achieving suitable film properties, 25 mol% or more (e.g., 28 mol% or more) is appropriate, preferably 30 mol% or more, and can be 35 mol% or more, or 40 mol% or more. The technology disclosed herein is preferably implemented in a manner where the acrylonitrile content in the total monomer component constituting polymer (A) is greater than 50 mol%. Furthermore, from the viewpoint of the flexibility of the coating material, the acrylonitrile content is appropriate to be 60 mol% or less, preferably less than 60 mol%. In some embodiments, the acrylonitrile content can be 57 mol% or less, or 56 mol% or less. The technology disclosed herein can also be implemented in a manner where the acrylonitrile content is 53 mol% or less, 50 mol% or less, or even 40 mol% or less.

[0080] The monomer (m) in the above monomer components T ) and the above monomers (m L molar ratio (m) T / m L There are no specific limitations; for example, it can be around 0.05 to 3.00, or around 0.10 to 2.00. In some methods, the above ratio (m) T / m L For example, a value of 0.60 or higher and 1.50 or lower, or 0.8 or higher and 1.5 or lower, is suitable. When using a polymer (A) composed of monomer components of this composition, coating materials exhibiting the preferred storage modulus described later are readily obtained. In some embodiments, the above ratio (m...) T / m L Preferably less than 1.5, more preferably 1.4 or less, and can be 1.35 or less, 1.30 or less, or 1.25 or less. Furthermore, in some embodiments, the above ratio (m) T / m L The preferred value is 0.70 or higher, more preferably 0.75 or higher, and can be 0.90 or higher, 1.0 or higher, or even greater than 1.0. This allows for a coating material that achieves a better balance between good peelability and good peelability of the self-coated film. The above ratio (m) T / m L The value can be 1.1 or higher, 1.15 or higher, or 1.20 or higher.

[0081] The monomer components constituting polymer (A) may also include monomers other than (m T ) and monomers (m L Monomers other than those in the homopolymer, i.e., monomers whose glass transition temperature is higher than -30℃ and lower than 90℃ (hereinafter referred to as monomers (m)). I )).

[0082] As a monomer (m I For example, monomers whose glass transition temperatures of homopolymers fall within the aforementioned range can be selected from the various monomers mentioned above, but are not limited to these. Monomer (m I One type can be used alone, or two or more types can be used in combination. It can be used as a single unit (m) I Non-limiting examples of monomers used include ethyl acrylate (EA), ethyl methacrylate, methyl acrylate (MA), n-butyl methacrylate, isobutyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, cyclohexyl acrylate, cyclohexyl methacrylate, vinyl acetate, N-vinyl-2-pyrrolidone, etc.

[0083] monomer (m) I The dosage of ) can remove monomers (m) from the total monomer component when the total amount of the monomer component is set at 100 mol%. T ) and monomers (m L The amount (mol%) should be set within a range below the specified amount. In some methods, the monomer (m) I It is appropriate for the amount of the monomer component to be no more than 80 mol% (e.g., no more than 40 mol%) of the total monomer component, it is advantageous to be no more than 30 mol%, preferably no more than 20 mol%, and more preferably no more than 15 mol%. The technology disclosed herein can preferably be used with monomers (m I The amount of monomer used is 0 mol% or more and less than 10 mol% of the total monomer components, for example, 0 mol% or more and less than 5 mol%. Here, monomer (m I The amount of monomer used is 0 mol% of the total monomer component, which means that at least no monomer (m) is intentionally used. I ).

[0084] <Synthesis of Polymer (A)>

[0085] There are no particular limitations on the method for obtaining polymer (A) from the monomer components described above. For example, known polymerization methods such as emulsion polymerization, solution polymerization, bulk polymerization, and suspension polymerization can be appropriately employed. Alternatively, photopolymerization by irradiation with UV light (typically carried out in the presence of a photopolymerization initiator), or radiation polymerization by irradiation with β-rays, γ-rays, or other radiation can also be used. In some preferred embodiments, polymer (A) is obtained by emulsion polymerization of monomer components with the composition described above. As for the monomer supply method in emulsion polymerization, a one-time feeding method in which all monomer raw materials are supplied at once, a continuous supply (dropleting) method, or a batch supply (dropleting) method can be appropriately employed. Alternatively, a portion or all of the monomer components can be pre-mixed with water and an emulsifier and emulsified, and the emulsion can be supplied to the polymerization vessel.

[0086] The polymerization temperature can be appropriately selected based on the type of monomer and solvent used, the type of polymerization initiator, etc. A polymerization temperature of about 20°C or higher is suitable, preferably about 40°C or higher, more preferably about 50°C or higher, and can be set to about 60°C or higher, or about 65°C or higher, and further, about 70°C or higher. Additionally, a polymerization temperature of about 170°C or lower (typically about 140°C or lower) is suitable, and preferably about 95°C or lower (e.g., about 85°C or lower). In emulsion polymerization, a polymerization temperature of about 95°C or lower (e.g., about 85°C or lower) is preferred.

[0087] The solvent used in solution polymerization (polymerization solvent) can be appropriately selected from conventionally known organic solvents. For example, aromatic compounds such as toluene (typically aromatic hydrocarbons), acetates such as ethyl acetate, and aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane are preferred.

[0088] During polymerization, known or commonly used thermal polymerization initiators and photopolymerization initiators can be used, depending on the polymerization method and polymerization mode. A single polymerization initiator can be used alone, or two or more can be used in appropriate combinations.

[0089] There are no particular limitations on the type of initiator used for thermal polymerization. For example, azo polymerization initiators, peroxide initiators, redox initiators based on combinations of peroxides and reducing agents, and substituted ethane initiators can be used.

[0090] Examples of azo initiators include 2,2'-azobisisobutyronitrile, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropanediamine] hydrate, 2,2'-azobis(2-methylpropanediamine) disulfate, 2,2'-azobis(2-methylpropanediamine) dihydrochloride, 2,2'-azobis(2-methylpropanediamine) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, and 2,2'-azobis(N,N'-dimethyleneisobutylamidine) dihydrochloride.

[0091] Examples of peroxide-based initiators include persulfates such as potassium persulfate and ammonium persulfate; benzoyl peroxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, dicumyl peroxide, dilauroyl peroxide, di-n-octanoyl peroxide, di(4-methylbenzoyl) peroxide, tert-butyl peroxide, tert-butyl isobutyrate, tert-hexyl peroxypentanoate, tert-butyl peroxypentanoate, and dicarbonic acid peroxide. Di(2-ethylhexyl) ester, di(4-tert-butylcyclohexyl) peroxydicarbonate, disec-butyl peroxydicarbonate, tert-butyl peroxyneodecanate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclododecane, 1,1-bis(tert-hexylperoxy)cyclohexane, hydrogen peroxide, etc.

[0092] Examples of redox initiators include combinations of peroxides and ascorbic acid (such as combinations of hydrogen peroxide and ascorbic acid), combinations of peroxides and iron(II) salts (such as combinations of hydrogen peroxide and iron(II) salts), and combinations of persulfates and sodium bisulfite.

[0093] There are no particular limitations on the photopolymerization initiator, and it can be used for example, ketal-based photopolymerization initiators, acetophenone-based photopolymerization initiators, benzoin ether-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, α-keto alcohol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzoyl-based photopolymerization initiators, thioxanone-based photopolymerization initiators, etc.

[0094] The amount of polymerization initiator can be set to the usual amount corresponding to the polymerization method and polymerization mode, without particular limitation. For example, about 0.001 to 5 parts by weight (typically about 0.01 to 2 parts by weight, for example about 0.01 to 1 part by weight) of polymerization initiator can be used relative to 100 parts by weight of the monomer to be polymerized.

[0095] During polymerization, various known chain transfer agents can be used as needed (they can also be used as molecular weight regulators or degree of polymerization regulators). A single chain transfer agent can be used, or two or more can be used in combination. Thiols such as n-dodecyl mercaptan, tert-dodecyl mercaptan, and mercaptoacetic acid can be used as chain transfer agents. Alternatively, chain transfer agents without sulfur atoms (non-sulfur chain transfer agents) can also be used. Specific examples of non-sulfur chain transfer agents include anilines such as N,N-dimethylaniline and N,N-diethylaniline; terpenoids such as α-pinene and terpinolene; styrene compounds such as α-methylstyrene and α-methylstyrene dimer; compounds with benzylidene groups such as dibenzylideneacetone, cinnamyl alcohol, and cinnamaldehyde; hydroquinones such as hydroquinone and naphthohydroquinone; quinones such as benzoquinone and naphthoquinone; alkenes such as 2,3-dimethyl-2-butene and 1,5-cyclooctadiene; alcohols such as phenol, benzyl alcohol, and allyl alcohol; and benzyl hydrogen compounds such as diphenylbenzene and triphenylbenzene.

[0096] When using a chain transfer agent, its amount relative to 100 parts by weight of the monomer component can be set to, for example, about 0.01 to 1 part by weight. The technology disclosed herein can also preferably be implemented without using a chain transfer agent.

[0097] Emulsion polymerization is typically carried out in the presence of an emulsifier. There are no particular restrictions on the emulsifier used in emulsion polymerization; well-known anionic emulsifiers, nonionic emulsifiers, etc., can be used. One emulsifier can be used alone, or two or more can be used in combination.

[0098] Examples of non-limiting anionic emulsifiers include sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzene sulfonate, polyoxyethylene sodium lauryl sulfate, polyoxyethylene alkyl ether sulfate, polyoxyethylene alkylphenyl ether ammonium sulfate, polyoxyethylene alkylphenyl ether sulfate, and polyoxyethylene alkyl sulfosuccinate. Examples of non-limiting nonionic emulsifiers include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene fatty acid esters, and polyoxyethylene polyoxypropylene block polymers. Emulsifiers with reactive functional groups (reactive emulsifiers) can be used. Examples of reactive emulsifiers include free radical polymerizable emulsifiers that incorporate free radical polymerizable functional groups such as propylene groups and allyl ether groups into the above-mentioned anionic or nonionic emulsifiers.

[0099] The amount of emulsifier used in emulsion polymerization can be, for example, 0.2 parts by weight or more, 0.5 parts by weight or more, 1.0 parts by weight or more, or 1.5 parts by weight or more, relative to 100 parts by weight of the monomer component. From the viewpoint of suppressing foaming of the composition containing the resulting emulsion during emulsion polymerization, in some methods, it is generally appropriate to set the amount of emulsifier to 10 parts by weight or less relative to 100 parts by weight of the monomer component, preferably 5 parts by weight or less, and also 3 parts by weight or less.

[0100] Emulsion polymerization can be carried out in the presence of a protective colloid. Examples of protective colloids include, for example, partially saponified polyvinyl alcohol (PVC), fully saponified PVC, modified PVC, and other PVC-based polymers; cellulose derivatives such as hydroxyethyl cellulose, hydroxypropyl cellulose, and carboxymethyl cellulose salts; and natural polysaccharides such as guar gum. The degree of saponification of partially saponified PVC is typically less than 95 mol%, and can be less than 92 mol% or less than 90 mol%. There is no particular limitation on the lower limit of the degree of saponification of partially saponified PVC; from the viewpoint of emulsion stability, a degree of 65 mol% or more is appropriate, preferably 70 mol% or more, and more preferably 80 mol% or more (e.g., 85 mol% or more). Examples of the aforementioned modified PVC include anionic modified PVC with anionic groups such as carboxyl groups and sulfonic acid groups; and cationic modified PVC with cationic groups such as quaternary ammonium salts. The degree of saponification of modified PVC is, for example, less than 98 mol%, and can be less than 95 mol%, less than 92 mol%, or less than 90 mol%. Furthermore, the lower limit of the degree of saponification of modified polyvinyl alcohol can be, for example, 55 mol% or more, and from the viewpoint of emulsion stability, 65 mol% or more is appropriate, preferably 70 mol% or more, and more preferably 80 mol% or more (e.g., 85 mol% or more). A single protective colloid can be used alone, or two or more can be used in combination.

[0101] The amount of protective colloid used is preferably about 0.1 parts by weight or more per 100 parts by weight of monomer components, and more preferably 0.5 parts by weight or more (e.g., 0.7 parts by weight or more). It is also preferably 10 parts by weight or less, and more preferably 5 parts by weight or less (e.g., 3 parts by weight or less, or 2 parts by weight or less). The protective colloid is preferably used in combination with an emulsifier as described above, but is not limited thereto; it can also be used without an emulsifier. For example, emulsion polymerization can be carried out by adding water and the protective colloid to a polymerization container, and supplying an emulsion obtained by pre-mixing and emulsifying a portion or all of the monomer components with water and an emulsifier to the polymerization container. It should be noted that when using anionic protective colloids (e.g., anionic modified polyvinyl alcohol) and emulsifiers in combination, from the viewpoint of polymerization stability, it is preferable to use one or more emulsifiers selected from the group consisting of anionic and nonionic emulsifiers.

[0102] In some preferred embodiments, emulsion polymerization is carried out in the presence of a polyvinyl alcohol-based polymer. The aqueous emulsion of polymer (A) obtained by this emulsion polymerization tends to readily exhibit the thickening effect provided by the addition of a thickener. By using such an aqueous emulsion of polymer (A), coating compositions exhibiting good viscosity characteristics suitable for slot die coating can be suitably prepared. Suitable examples of polyvinyl alcohol-based polymers include anionic modified polyvinyl alcohol. For example, sulfonic acid-modified polyvinyl alcohol and carboxyl-modified polyvinyl alcohol are preferred. Polyvinyl alcohol-based polymers and emulsifiers can be used in combination.

[0103] <Coating Composition>

[0104] The coating compositions disclosed herein contain any of the aforementioned polymers (A) as base polymers. The form of the coating compositions is not particularly limited; for example, they may be aqueous emulsion-type compositions in which polymer (A) is dispersed in an aqueous solvent, solvent-type compositions in which polymer (A) is dissolved in an organic solvent, etc. From an environmental hygiene perspective, aqueous emulsion-type coating compositions are preferred. The following description primarily focuses on aqueous emulsion-type coating compositions, but it is not intended to limit the coating compositions disclosed herein to aqueous emulsion types.

[0105] In aqueous emulsion-type coating compositions, the aforementioned aqueous solvent refers to water or a mixed solvent in which water is the main component (containing more than 50% by weight). The solvent other than water constituting this mixed solvent can be one or more selected from various organic solvents (such as lower alcohols) capable of homogeneous mixing with water. Typically, in the aqueous solvent described in this specification, the proportion of water is 90% by weight or more, preferably 95% to 100% by weight.

[0106] The coating compositions disclosed herein may contain various additives as desired. Examples of such additives include known thickeners, thixotropic agents, dispersants, defoamers, and inorganic powders. For example, various additives can be blended into an aqueous emulsion (polymerization reaction liquid) of the polymer (A) obtained by emulsion polymerization as described above, thereby preparing an aqueous emulsion-type coating composition. Alternatively, the aqueous emulsion of the polymer (A) can be used directly, or the aqueous emulsion can be adjusted by pH (e.g., by adding ammonia to adjust the pH to about 6-8) and / or concentration (e.g., by adding water to adjust the solid content to about 40-60% by weight) and used as a coating composition.

[0107] By including inorganic powder in the coating composition, a coating material containing inorganic powder is formed. Using this coating material, the inorganic powder blocks ultraviolet light, thus suppressing photodegradation of both the coating material itself and the coating film protected by it. As inorganic powders, oxides such as titanium oxide, zinc oxide, magnesium oxide, aluminum oxide, and silicon dioxide can be used; carbonates such as calcium carbonate; and sulfates such as barium sulfate. Preferably, the inorganic powder can be colored white. Using a white coating material can, for example, suppress temperature rise caused by sunlight exposure, thereby better suppressing the degradation of both the coating material and the coating film.

[0108] The amount of inorganic powder relative to 100 parts by weight of polymer (A) can be, for example, 0.5 parts by weight or more. From the viewpoint of light-shielding effect, it is appropriate to set it to 1 part by weight or more, preferably 2 parts by weight or more, more preferably 3 parts by weight or more, and can be 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, or 30 parts by weight or more, 35 parts by weight or more, or 40 parts by weight or more (e.g., 45 parts by weight or more). In addition, the amount of inorganic powder relative to 100 parts by weight of polymer (A) can be, for example, 100 parts by weight or less. From the viewpoint of the strength and film-forming properties of the coating material, it is appropriate to set it to 80 parts by weight or less, and advantageous to set it to 60 parts by weight or less. It is preferably 50 parts by weight or less, and can be 40 parts by weight or less, 30 parts by weight or less, 20 parts by weight or less, or 15 parts by weight or less, or 10 parts by weight or less.

[0109] In some preferred embodiments, the aforementioned inorganic powder contains at least titanium oxide (TiO2). The titanium oxide can be used in combination with one or more other inorganic powders (e.g., calcium carbonate). The type of titanium oxide is not particularly limited, and titanium oxides of any crystalline form, such as rutile, anatase, or brookite, can be used. Rutile titanium oxides are preferred. Titanium oxides with a surface coating treatment on the particles can be used. The material of the coated titanium oxide particles is not particularly limited; for example, it can be inorganic oxides such as silica, alumina, or zinc oxide. As a suitable example, a high-weather-resistant titanium oxide (typically rutile titanium oxide) with a particle surface coated with Si-Al2O3 can be used.

[0110] The amount of titanium oxide relative to 100 parts by weight of polymer (A) can be, for example, 0.1 parts by weight or more. From the viewpoint of light-shielding effect, it is appropriate to set it to 0.5 parts by weight or more, preferably 1 part by weight or more, more preferably 2 parts by weight or more, and may also be 3 parts by weight or more. In addition, the amount of titanium oxide relative to 100 parts by weight of polymer (A) can be, for example, 30 parts by weight or less, 20 parts by weight or less, preferably 15 parts by weight or less, may be 10 parts by weight or less, and may also be 8 parts by weight or less.

[0111] The average particle size of the inorganic powder is not particularly limited. For example, from the viewpoint of obtaining good light-shielding effect, the average particle size of the inorganic powder is preferably 150 nm or more, more preferably 180 nm or more, and can be 220 nm or more, or 250 nm or more. On the other hand, from the viewpoint of dispersibility in the resin composition, the average particle size of the inorganic powder is suitable as 3000 nm or less (2000 nm or less), preferably 1500 nm or less, more preferably 1000 nm or less (e.g., 800 nm or less), and can be 500 nm or less, 400 nm or less, or 350 nm or less. For example, titanium oxide particles with an average particle size of about 250 to 350 nm are preferably used.

[0112] Thickeners help to adjust the viscosity characteristics of coating compositions. Known thickeners, such as urethane-based, cellulose-based, polyether-based, and acrylic-based thickeners, can be used as thickeners. A single thickener can be used alone, or two or more can be used in combination.

[0113] Commercially available products as urethane-based thickeners include, for example, BYK's products under the trade names "RHEOBYK-H3300VF", "RHEOBYK-T 1010", and "RHEOBYK-L 1400"; ADEKA's products under the trade names "ADEKA NOL UH-450VF", "ADEKA NOL UH-420", "ADEKA NOL UH-462", "ADEKA NOL UH-472", "ADEKA NOL UH-540", "ADEKA NOL UH-756VF", and "ADEKA NOL UH-814N"; and San Nopco Limited's products under the trade names "SN Thickener 612", "SN THICKENER 621N", "SN THICKENER 625N", "SN THICKENER 627N", and "SN THICKENER 660T". In some methods, urethane-associated thickeners are preferred as urethane-based thickeners. Suitable examples of urethane-associated thickeners include BYK's products under the trade names "RHEOBYK-H 3300VF", "RHEOBYK-T 1010", and "RHEOBYK-L 1400", and ADEKA's products under the trade names "ADEKA NOL UH-450VF", "ADEKA NOL UH-420", and "ADEKA NOL UH-756VF".

[0114] Examples of cellulose-based thickeners include hydroxyethyl cellulose, carboxymethyl cellulose, and methyl cellulose. Commercially available products include, for example, the brand name "SANHEC L" manufactured by Sansho Co., Ltd.

[0115] Examples of polyether-based thickeners include polyethylene glycol, polyether dialkyl esters, polyether dialkyl ethers, and polyether epoxy modifiers. Commercially available products include, for example, "POLYOX WSRN-80" manufactured by Dow Chemical Company.

[0116] Examples of acrylic thickeners include acrylic polymers such as sodium polyacrylate. Commercially available examples include products manufactured by Rohm and Haas Company under the trade names "Primal ASE-60," "Primal TT-615," and "Primal RM-5," ​​and products manufactured by San Nopco Limited under the trade names "SN THICKENER 613," "SN THICKENER 618," "SN THICKENER 630," "SN THICKENER 634," and "SN THICKENER 636."

[0117] The amount of thickener is not particularly limited and can be appropriately adjusted to obtain the desired viscosity characteristics. From the viewpoint of suppressing excessive influence on film properties, in some embodiments, it is appropriate to set the amount of thickener relative to 100 parts by weight of polymer (A) to be 15 parts by weight or less, preferably 10 parts by weight or less, more preferably 5 parts by weight or less (e.g., 3 parts by weight or less), 2.5 parts by weight or less, 2 parts by weight or less, 1.0 parts by weight or less, or 0.50 parts by weight or less. There is no particular limitation on the lower limit of the amount of thickener, for example, it can be 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more (e.g., 0.10 parts by weight or more), or 0.20 parts by weight or more relative to 100 parts by weight of polymer (A).

[0118] Thixotropic agents can help adjust the viscosity properties of coating compositions. Examples of thixotropic agents include inorganic materials such as bentonite, modified bentonite, montmorillonite, and lithium montmorillonite. A single thixotropic agent can be used, or two or more can be used in combination.

[0119] The amount of thixotropic agent is not particularly limited and can be appropriately adjusted to obtain the desired viscosity characteristics. From the viewpoint of suppressing excessive influence on film properties, in some embodiments, it is appropriate to set the amount of thixotropic agent relative to 100 parts by weight of polymer (A) to be 10 parts by weight or less, preferably 5 parts by weight or less, 3 parts by weight or less, 2.5 parts by weight or less, or 2 parts by weight or less. There is no particular limitation on the lower limit of the amount of thixotropic agent; for example, relative to 100 parts by weight of polymer (A), it can be 0.01 parts by weight or more, 0.05 parts by weight or more, or 0.1 parts by weight or more. Alternatively, thixotropic agent may not be used.

[0120] Thixotropic agents can also function as thickeners. Thickeners and thixotropic agents as described above can be used in combination or individually. When thickeners and thixotropic agents are used in combination, their total amount relative to 100 parts by weight of polymer (A) can be, for example, 15 parts by weight or less, 10 parts by weight or less, 5 parts by weight or less, 4 parts by weight or less, 2.5 parts by weight or less, 1.5 parts by weight or less, or 1.0 parts by weight or less; or more than 0.01 parts by weight, 0.05 parts by weight or more, 0.1 parts by weight or more (e.g., 0.10 parts by weight or more), or 0.20 parts by weight or more.

[0121] As a method for applying a coating composition to a coating film on a protected object, coating machines such as die-casting machines, sprayers, and dip coating can be used. The aforementioned die-casting machine coating can be performed using a coating system that includes a robotic arm equipped with a slit die. For example, by controlling the robotic arm to spray the coating composition into a continuous liquid film (ribbon) and moving the slit die along the shape of the protected object, the coating composition can be applied efficiently and accurately to the protected object even if it has a non-planar shape (e.g., a complex three-dimensional shape such as a car body panel).

[0122] From the perspective of maximizing the efficiency and precision of coating material formation, the drying of the coating composition is preferably carried out under heating. The drying temperature can be set to approximately 40°C to 100°C, and is typically preferred to be set to approximately 60°C to 90°C.

[0123] While not specifically limited, from the viewpoint of ease of coatability and film thickness management, a solid content of approximately 25–75% by weight in the coating composition is appropriate, preferably approximately 30–70% by weight (e.g., approximately 45–55% by weight). The solid content can be adjusted by the amount of solvent (e.g., an aqueous solvent). For example, the solid content of the coating composition can be adjusted by regulating the amount of water used in the emulsion polymerization or by adding water after the emulsion polymerization is completed.

[0124] The thickness of the protective coating material is not particularly limited, but from the viewpoint of improving the protective effect, 20 μm or more is appropriate. From the viewpoint of strength and peelability, 50 μm or more is preferred, and more preferably 70 μm or more (e.g., 85 μm or more). The thickness of the coating material can be adjusted by the coating amount and solid content of the coating composition. From the viewpoint of the drying properties and anti-sagging properties of the coating composition, a coating material thickness of 300 μm or less is appropriate, preferably 200 μm or less, and more preferably 150 μm or less.

[0125] (BH viscosity)

[0126] In some methods, it is appropriate for the viscosity V1 of the coating composition, measured using a BH type viscometer at 2 rpm, to be 20 Pa·s or higher, preferably 40 Pa·s or higher, and more preferably 55 Pa·s or higher. As the viscosity V1 measured under such low shear rate conditions increases, the anti-sagging properties of the coating composition applied to the protected object (e.g., anti-sagging properties when applied to a vertical surface) tend to improve. On the other hand, from the viewpoint of the defoaming and leveling properties of the coating composition, it is appropriate for the viscosity V1 of the coating composition to be 200 Pa·s or lower, preferably 150 Pa·s or lower, and more preferably 100 Pa·s or lower (e.g., 80 Pa·s or lower).

[0127] The viscosity V2 of the above-mentioned coating composition, measured using a BH-type viscometer at 20 rpm, is not particularly limited, and can be, for example, around 5 Pa·s to 50 Pa·s. When the viscosity V2 is within the above range, the above-mentioned viscosity V1 is easily obtained. The viscosity of the coating composition obtained using a BH-type viscometer (BH viscosity) is measured using a BH-type viscometer at 30°C at 2 rpm and 20 rpm. The rotor used in the measurement is appropriately selected according to the viscosity. For example, rotor No. 6 can be used for measurement; if rotor No. 6 is not suitable, other suitable rotor numbers can be used for measurement.

[0128] The ratio of viscosity V1 to viscosity V2 (hereinafter also referred to as the "Ti value") can be, for example, 2.0 or more, preferably 3.0 or more, and preferably 3.5 or more. Furthermore, the Ti value can be, for example, 9.0 or less, preferably 8.0 or less, more preferably 7.0 or less, 6.0 or less, or 5.5 or less. When using a coating composition having such a Ti value, it is easy to obtain coatability suitable for slot die coating.

[0129] (Rheometer viscosity)

[0130] In some methods, the shear rate of the above-mentioned coating composition was measured using a cone-plate rheometer at 100 sec. -1The viscosity V3 is preferably 1.0 Pa·s or more, more preferably 1.3 Pa·s or more, and can be 1.5 Pa·s or more, 2.0 Pa·s or more, or 2.3 Pa·s or more. By ensuring that the viscosity V3 measured under the high shear rate conditions is at or above the specified value, the coatability (mold coating property) of the slit mold can be improved. There is no particular upper limit to the viscosity V3, but from the viewpoints of ease of defoaming and ease of liquid delivery, a value of 15 Pa·s or less is appropriate, preferably 10 Pa·s or less, and can be 8.5 Pa·s or less, or 6.0 Pa·s or less. The viscosity of the coating composition obtained by the rheometer (rheometer viscosity) can be determined as follows: using a commercially available rheometer (e.g., the Rheo Stress 1 rheometer manufactured by Harco Co., Ltd. or its equivalent), using a conical rotor (Cone Diameter: 35 mm, Cone Angle: 0.5 degrees), and based on a shear rate of 0.1 to 2000 seconds at 30°C. -1 Viscosity under continuous variation, reading shear rate 100 sec -1 The viscosity was determined accordingly.

[0131] <Coating Protective Materials>

[0132] The protective coating material disclosed herein is formed using the coating composition described above. For example, the coating composition is applied (preferably using a slit mold) to the coating film on the object to be protected and then allowed to dry. Thus, for example, as... Figure 1 As shown, a protective coating material 10 formed from the above-described coating composition can be applied to the coating 22 of the protected object 20 having the coating 22.

[0133] In some embodiments, the storage modulus (G'(70)) of the coating material at 70°C can be, for example, 0.20 MPa or more. From the viewpoint of peelability, it is appropriate for G'(70) to be 0.30 MPa or more, preferably 0.40 MPa or more, and more preferably 0.45 MPa or more. Even at temperatures higher than normal, such as when the object to be protected by the coating material is placed outdoors in summer, the coating material with a specified G'(70) will not become excessively soft and can be properly peeled off from the film. From the viewpoint of improving peelability at high temperatures, it is advantageous for G'(70) to be 0.50 MPa or more, preferably 0.70 MPa or more, and can be 1.0 MPa or more, or 1.2 MPa or more. There is no particular upper limit to G'(70), for example, it can be 5 MPa or less, preferably 3 MPa or less, 2.5 MPa or less, or 2.0 MPa or less. In some methods, G'(70) can be 1.5 MPa or less, 1.30 MPa or less, or 1.2 MPa or less (e.g., 1.20 MPa or less). It is preferable from the viewpoint that G'(70) is not too high to suppress trace adhesion to the coating.

[0134] In some embodiments, the storage modulus (G'(23)) of the coating material at 23°C can be, for example, 100 MPa or more. From the viewpoint of peelability, G'(23) is preferably 150 MPa or more, more preferably 180 MPa or more, and can be 230 MPa or more, 250 MPa or more, 300 MPa or more, 450 MPa or more, or 500 MPa or more. Coating materials with a specified G'(23) or higher tend to be less prone to breakage or excessive elongation when peeled off from the coating at room temperature. This is advantageous from the viewpoint of improving peelability. In some embodiments, G'(23) of about 1000 MPa or less is appropriate. It is advantageous from the viewpoint of suppressing trace adhesion to the coating if G'(23) is not too high. Furthermore, it is easier to perform operations that create a peeling opportunity (e.g., scraping the end of the coating material with a fingernail to make it float off the coating) when peeling the coating material from the coating, so this is also preferred from the viewpoint of peelability. In some methods, G'(23) can be below 800MPa, below 700MPa, below 600MPa, below 500MPa, below 450MPa, or below 400MPa.

[0135] In some embodiments, the storage modulus (G'(-30)) of the aforementioned coating material at -30°C can be, for example, about 2400 MPa or less. From the viewpoint of preventing trace adhesion, it is appropriate for G'(-30) to be 2300 MPa or less, advantageous to be 2200 MPa or less (e.g., less than 2200 MPa), preferably 2000 MPa or less, more preferably 1900 MPa or less, and can be 1800 MPa or less, 1700 MPa or less, or 1600 MPa or less. The lower limit of G'(-30) is not particularly limited. From the viewpoint of easily forming coating materials with G'(70) and G'(23) in a suitable range, in some embodiments, it is appropriate for G'(-30) to be 500 MPa or more, preferably 800 MPa or more, more preferably 1000 MPa or more, and can be 1200 MPa or more, 1300 MPa or more, or 1400 MPa or more.

[0136] The storage modulus (G'(70), G'(23), G'(-30)) of the coating material was determined using the method described in the examples below.

[0137] In some of the coating materials disclosed herein, it is suitable for the glass transition temperature (hereinafter also referred to as "RSA-Tg") of the coating material, which is determined in the form of the peak temperature of tanδ in a viscoelastic measurement, to be 20°C or higher, preferably 30°C or higher, and more preferably 34°C or higher. Furthermore, the RSA-Tg can be, for example, 50°C or lower, 45°C or lower, or 43°C or lower (e.g., 41°C or lower). Using coating materials with RSA-Tg within the above-mentioned range, it is easy to obtain coating materials in suitable ranges for one or more of the aforementioned G'(70), G'(23), and G'(-30).

[0138] For some coating materials, a glass transition temperature (hereinafter also referred to as "RSA-Tg(G")") determined in the form of the temperature corresponding to the inflection point of the loss modulus G” in the viscoelasticity measurement is preferably 5°C or higher, more preferably 15°C or higher, and more preferably 20°C or higher. In addition, RSA-Tg(G”) can be, for example, 40°C or lower, 35°C or lower, or 30°C or lower (e.g., 25°C or lower). With a film-protecting coating material with RSA-Tg(G”) in the above range, a film-protecting coating material that satisfies the above G'(23) and G'(70) can be easily obtained. It should be noted that the RSA-Tg(G”) of Examples B1 to B6 in the following embodiments are as follows: B1: 20°C, B2: 20°C, B3: 20°C, B4: 20°C, B5: 23°C, B6: 23°C.

[0139] The coating material disclosed herein, when tested by tensile tests as described in the embodiments below, is suitable if its breaking strength is 12 N / 25 mm or more, advantageous if it is 15 N / 25 mm or more, preferably 20 N / 25 mm or more, and may also be 25 N / 25 mm or more, 30 N / 25 mm or more, or 35 N / 25 mm or more.

[0140] The coating material disclosed herein, as determined by the tensile test described in the later embodiments, exhibits an elongation at break of 100% or more, which is suitable, 150% or more is advantageous, preferably 200% or more, and can be 220% or more, or even 250% or more. Such a coating material, due to moderate deformation during peeling and removal from the coating film, can disperse stress, thus suppressing damage to the coating material caused by localized stress concentration. There is no particular upper limit to the elongation at break; for example, 500% or less is suitable, and can be 450% or less, or even 400% or less. Maintaining a moderate elongation at break is advantageous from the viewpoint of improving peeling efficiency.

[0141] From the viewpoint of obtaining good peelability, it is appropriate for the peel strength of the coating material disclosed herein to be less than 4.0 N / 25 mm, and advantageous to be less than 2.5 N / 25 mm, as measured using the method described in the examples below. In some embodiments, the peel strength is preferably 2.0 N / 25 mm or less, more preferably 1.5 N / 25 mm or less, and can be 1.2 N / 25 mm or less, or 1.0 N / 25 mm or less. Low peel strength is preferred from the viewpoint of reducing the workload during peeling, and is also advantageous from the viewpoint of suppressing breakage and damage of the coating material during peeling. Furthermore, from the viewpoint of obtaining adequate adhesion to the coating film, a peel strength of 0.1 N / 25 mm or more is appropriate, preferably 0.2 N / 25 mm or more, and can be 0.3 N / 25 mm or more, 0.5 N / 25 mm or more, or 0.7 N / 25 mm or more. Not having a peel strength that is not too low is preferred from the viewpoint of preventing the coating material from unintentionally peeling off from the coating film during the protection period.

[0142] In some methods, it is appropriate for the fracture strength [N / 25mm] to be 5 times or more than the peel strength [N / 25mm], advantageous to be 8 times or more, and preferably 10 times or more. When the ratio of fracture strength to peel strength increases, there is a tendency for breakage or damage to occur less easily when peeling the coating from the protected object. From this viewpoint, the ratio of fracture strength to peel strength can be 15 or more, 20 or more, 25 or more, 30 or more, 35 or more, or 40 or more. There is no particular upper limit to the ratio of fracture strength to peel strength; from the viewpoint of easily balancing moderate peel strength and good anti-marking adhesion, a ratio of 100 or less is appropriate, and it can be 80 or less, 70 or less, or 60 or less.

[0143] According to this specification, an aqueous emulsion is provided, which is an aqueous emulsion of any polymer (A) disclosed herein dispersed in an aqueous solvent, as a component of any coating composition disclosed herein, and can be used to manufacture the coating composition. The coating composition disclosed herein can be suitably manufactured by adding the various components described above (e.g., thickeners, inorganic powders, thixotropic agents) to the aqueous emulsion as needed and mixing. Alternatively, the aqueous emulsion described above can also be used directly as a coating composition.

[0144] According to this specification, a coating protection method may be provided, comprising: preparing any coating composition disclosed herein, applying the coating composition onto the coating of a protected object having a coating, and drying the coating composition to form a coating protective coating material that temporarily protects the coating.

[0145] Reference Figure 2 One embodiment of the above-described coating protection method will be described. Specifically, any coating composition disclosed herein is prepared (step S10). The coating composition is applied (e.g., using a slit mold) onto the coating of the object to be protected, which has a coating film (step S20). The applied coating composition is dried to form a coating protective coating material that temporarily protects the coating film (step S30). By applying the coating material to the coating film in this way, the coating film can be protected from damage and deterioration. It should be noted that the protective coating material is peeled off from the coating film at a desired time (e.g., peeled off) (step S40).

[0146] The matters disclosed in this specification include the following.

[0147] [1] A protective coating material, which is a protective coating material formed from a liquid coating composition.

[0148] The above coating composition comprises polymer (A) as a base polymer, wherein polymer (A) is a polymer containing acrylic monomer components.

[0149] The SP value of the polymer (A) is 9.8 (cal / cm). 3 ) 1 / 2 The above, and

[0150] The glass transition temperature of the polymer (A) calculated based on the composition of the monomer components constituting the polymer (A) is below 0°C.

[0151] [2] According to the coating protective coating material described in [1] above, wherein the acid value of the polymer (A) is less than 15 mg KOH / g.

[0152] [3] The protective coating material according to [1] or [2] above has a storage modulus of 0.40 MPa or above at 70°C.

[0153] [4] The coating protective coating material according to any one of [1] to [3] above, wherein the monomer component constituting the polymer (A) includes a nitrogen-containing monomer.

[0154] [5] The protective coating material according to any one of [1] to [4] above, wherein the nitrogen-containing monomer comprises acrylonitrile.

[0155] [6] The protective coating material according to any one of [1] to [5] above, wherein the glass transition temperature of the polymer (A) calculated based on the composition of the monomer components constituting the polymer (A) is -20°C or higher.

[0156] [7] The coating protective coating material according to any one of [1] to [6] above, wherein the monomer component constituting the polymer (A) includes an alkyl (meth)acrylate having an alkyl group having 1 to 3 carbon atoms at the ester end and a carboxyl-containing monomer.

[0157] [8] The coating protective coating material according to any one of [1] to [7] above, wherein the coating composition is a composition in the form of an aqueous emulsion of the polymer (A) dispersed in an aqueous solvent.

[0158] [9] The protective coating material according to any one of [1] to [8] above contains a polyvinyl alcohol polymer.

[0159]

[10] The protective coating material according to any one of [1] to [9] above contains a thickener.

[0160]

[11] The protective coating material according to any one of [1] to

[10] above further contains inorganic powder.

[0161]

[12] The coating protective coating material according to

[11] above, wherein the inorganic powder comprises titanium oxide.

[0162]

[13] The coating material according to any one of [1] to

[12] above has a thickness of 20 μm or more and 300 μm or less.

[0163]

[14] A coating composition for forming a protective coating material as described in any one of [1] to

[13] above.

[0164]

[15] A coating composition comprising a polymer (A) as a base polymer, said polymer (A) being a polymer comprising an acrylic monomer component.

[0165] The SP value of the polymer (A) is 9.8 (cal / cm). 3 ) 1 / 2 The above, and

[0166] The glass transition temperature of the polymer (A) calculated based on the composition of the monomer components constituting the polymer (A) is below 0°C.

[0167]

[16] According to the coating composition described in

[15] above, wherein the acid value of the polymer (A) is less than 15 mg KOH / g.

[0168]

[17] The coating composition according to

[15] or

[16] above has a storage modulus of 0.40 MPa or more at 70°C.

[0169]

[18] The coating composition according to any one of

[15] to

[17] above, wherein the monomer component constituting the polymer (A) comprises a nitrogen-containing monomer.

[0170]

[19] The coating composition according to any one of

[15] to

[18] above, wherein the glass transition temperature of the polymer (A) calculated based on the composition of the monomer components constituting the polymer (A) is -20°C or higher.

[0171]

[20] The coating composition according to any one of

[15] to

[19] above, wherein the monomer component constituting the polymer (A) includes an alkyl (meth)acrylate having an alkyl group having 1 to 3 carbon atoms at the ester end and a carboxyl-containing monomer.

[0172]

[21] The coating composition according to any one of

[15] to

[20] above is a composition in the form of an aqueous emulsion of the polymer (A) dispersed in an aqueous solvent.

[0173]

[22] The coating composition according to any one of

[15] to

[21] above, wherein the polymer (A) is obtained by emulsion polymerization in the presence of a protective colloid.

[0174]

[23] The coating composition according to

[22] above, wherein the protective colloid is a polyvinyl alcohol polymer.

[0175]

[24] The coating composition according to any one of

[15] to

[23] above contains a thickener.

[0176]

[25] The coating composition according to any one of

[15] to

[24] above further contains inorganic powder.

[0177]

[26] The coating composition according to

[25] above, wherein the inorganic powder comprises titanium oxide.

[0178]

[27] A coating protection method, comprising:

[0179] Prepare the coating composition described in any one of

[15] to

[26] above,

[0180] A protective coating material is formed by applying the coating composition onto the coating of a protected object having a coating film, and drying the coating composition to form a temporary protective coating film.

[0181]

[28] According to the coating protection method described in

[27] above, the coating composition is applied using a slit mold.

[0182] Example

[0183] The following describes some experimental examples related to the present invention, but it is not intended to limit the present invention to the specific examples shown. It should be noted that, in the following description, "parts" and "%" indicating dosage and content are by weight unless otherwise specified. Furthermore, unless otherwise specified, the amount of each material used is based on the amount of active ingredient.

[0184] Experimental Example 1

[0185] <Preparation of Coating Composition>

[0186] (Example A1)

[0187] A monomer emulsion was prepared by mixing 66.3 parts (52 mol%) of n-butyl acrylate (BA), 15.8 parts (30 mol%) of acrylonitrile (AN), 17.9 parts (18 mol%) of methyl methacrylate (MMA), 0.05 parts of lauryl mercaptan, 2 parts of sodium polyoxyethylene lauryl sulfate (Kao Corporation, trade name "LATEMUL E118B"), and 40 parts of deionized water, and emulsifying the mixture using an emulsifier (homogenizer) while purging it with nitrogen.

[0188] In a reaction vessel equipped with a condenser, nitrogen inlet pipe, thermometer, and stirrer, 50 parts of ion-exchanged water were placed, along with 1 part of anion-modified polyvinyl alcohol (GOHSENX L-3266, Nippon Synthetic Chemical Industry Co., Ltd.; saponification degree 86.5–89.0 mol%). While introducing nitrogen, the mixture was dissolved at room temperature, then heated to 60°C. 0.1 parts of 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropanediamine] hydrate (WAKU Pure Chemical Industries Co., Ltd., VA-057) were added as a polymerization initiator. The liquid temperature in the reaction vessel was maintained at approximately 60°C, and the monomer emulsion was added over 3 hours to initiate the polymerization reaction. After the monomer emulsion was added, the mixture was maintained at this temperature for 3 hours for maturation. After cooling the system to room temperature, the pH was adjusted to 7.5 by adding 10% ammonium water, yielding an aqueous emulsion of polymer A1, which is the monomer of the aforementioned polymer. The aqueous emulsion was used as the coating composition in this example.

[0189] (Examples A2 to A10)

[0190] By changing the types and amounts of monomers as shown in Table 1, aqueous emulsions (coating compositions) of polymers A2 to A10 in each example were obtained in the same manner as in Example 1. It should be noted that in Table 1, "VAc" represents vinyl acetate and "AA" represents acrylic acid.

[0191] <Measurement and Evaluation>

[0192] [Tension Test]

[0193] For a steel sheet coated with an acid-epoxy crosslinking acrylic coating (manufactured by KANSAIPAINT CO.,LTD., trade name "KINO1210TW"), the coated surface was kept horizontal. Using an applicator manufactured by TP Giken Co., Ltd., each example coating composition was applied to the coated surface (on the coating film) of the steel sheet and dried at 80°C for 3 minutes to form a thin film (coating protective coating material). The coating amount of the coating composition was set such that the thickness, converted from solid components, was 100 μm. The formed film was peeled off from the coated steel sheet at room temperature and cut into strips 25 mm wide and 100 mm long to prepare test samples for tensile testing.

[0194] The test samples were placed in a tensile testing machine (manufactured by Shimadzu Corporation, device name "Tensilon") at 23°C and 50% RH, and tensile tests were performed at a speed of 0.3 m / min with a mark distance of 50 mm. The breaking strength [N / 25 mm] and elongation at break were determined. The results are shown in Table 1.

[0195] [Storage Modulus Determination]

[0196] Using the coating compositions described in the examples, a film with a thickness of 100 μm was formed on the coated steel plate in the same manner as the film preparation for the tensile test described above. The formed film was peeled off from the coated steel plate at room temperature, and multiple sheets were overlapped and integrated by pressure to produce a laminated film with a thickness of approximately 1 mm. The test sample, which was prepared by punching a disc shape with a diameter of 7.9 mm using parallel plates, was tested using a viscoelastic testing machine (TA Instruments, device name "ARES G2"), with a shear strain at a frequency of 1 Hz in shear mode over a temperature range of -70 to 150 °C at a heating rate of 5 °C / min. The storage modulus G' at each temperature was determined. The results are shown in Table 1.

[0197] [Acid Value Determination]

[0198] Using the coating compositions described in the examples, a film with a thickness of 100 μm was formed on the coated steel plate in the same manner as the film preparation for the tensile test described above. The formed film was peeled off from the coated steel plate at room temperature, immersed in chloroform, and the resulting mixture was allowed to stand for 12 hours. The mixture was then filtered, and a substance with a weight-average molecular weight of 10,000 or more (determined by GPC) was used as the sample. The acid value was determined based on the potentiometric titration method specified in JIS K0070-1992. Specifically, the accurately weighed and taken sample was added to 50 mL of a solvent obtained by mixing diethyl ether and ethanol at a volume ratio of 4:1, and the sample was completely dissolved. Then, phenolphthalein solution was added as an indicator to prepare the test solution. Potentiometric titration was performed on this test solution using a 0.1 mol / L potassium hydroxide ethanol solution, and the inflection point of the resulting titration curve was taken as the endpoint. The acid value was calculated using the following formula. The results are shown in Table 1.

[0199] Acid value (mgKOH / g) = (B × F × 5.611) / S

[0200] B: The volume (mL) of 0.1 mol / L potassium hydroxide ethanol solution added at the endpoint.

[0201] F: 0.1 mol / L potassium hydroxide ethanol solution (1.0)

[0202] S: Sample size (g)

[0203] [Peel strength]

[0204] Using the coating compositions described in each example, a film with a thickness of 100 μm was formed on the coated steel plate in the same manner as the film preparation for the tensile test described above. Next, the coated steel plate was placed in a constant temperature bath at 70°C and maintained for 7 days. The coated steel plate was then removed from the constant temperature bath and maintained at 23°C and 50% RH for at least 30 minutes. Afterward, two straight slits (25 mm apart) and a slit perpendicular to the first slit were cut into the film. The film was partially peeled off from the second slit and placed in a tensile testing machine (manufactured by Shimadzu Corporation, device name "TENSILON") at a tensile speed of 0.3 m / min along a 180-degree direction. The peel strength [N / 25 mm] of the film from the coated steel plate was then measured. The results are shown in Table 1.

[0205] [Anti-mark adhesion]

[0206] Using the coating compositions described in the examples, and following the same procedure as for the film preparation used in the tensile test, a film with a thickness of 100 μm was formed approximately at the center of the coated steel sheet. The coated steel sheet was then placed in a constant temperature bath at 70°C and maintained for 7 days. After removing the coated steel sheet from the constant temperature bath and maintaining it at 23°C and 50% RH for at least 30 minutes, the film was peeled off the coated steel sheet, and the appearance of the coating at the location where the film was formed was visually observed. Based on these results, the anti-scratch adhesion was evaluated according to the following three criteria. A higher score indicates better anti-scratch adhesion. The results are shown in Table 1.

[0207] 3 points: No traces were found attached.

[0208] 2 points: Slight traces were observed immediately after the film was peeled off, but the traces disappeared naturally after being left at room temperature.

[0209] 1 point: Obvious traces were found, and the traces did not disappear even when placed at room temperature.

[0210] [Table 1]

[0211] Table 1

[0212]

[0213] As shown in Table 1, the peel strength of the films formed from Examples A1 to A8 is less than 4 N / 25 mm, indicating good peelability of the self-coated films. Furthermore, these films all exhibit good anti-scratch adhesion properties. It should be noted that among the films from Examples A1 to A8, the tensile strength / peel strength ratio of film A5 is 9, while the others are all above 10. Among these, the films from Examples A2 to A4 have low peel strength and tensile strength / peel strength ratios above 35, demonstrating excellent peelability. On the other hand, the films formed from the coating compositions of Examples A9 and A10 cannot simultaneously achieve good peelability and good anti-scratch adhesion properties.

[0214] Experiment Example 2

[0215] <Preparation of Coating Composition>

[0216] (Example B1)

[0217] In the coating composition of Example A1 prepared in Experimental Example 1, an antifoaming agent (manufactured by Kusunoki Chemical Co., Ltd., trade name "DISPARLON AQ7533") and a thickener (urethane associative thickener manufactured by ADEKA Co., Ltd., trade name "ADEKA NOL UH-756VF") were mixed in amounts shown in Table 1 relative to 100 parts of polymer A1 contained in the composition to obtain the coating composition of this example.

[0218] (Example B2)

[0219] In the coating composition of Example A1 prepared in Experimental Example 1, titanium oxide (rutile titanium oxide manufactured by Ishihara Sangyo Co., Ltd., trade name "TIPAQUE CR-95", average particle size 280 nm), dispersant (manufactured by BYK Co., Ltd., trade name "DISPERBYK-2015"), defoamer (manufactured by Kusunoki Chemical Co., Ltd., trade name "DISPARLON AQ7533") and thickener (urethane associative thickener manufactured by ADEKA Co., Ltd., trade name "ADEKA NOL UH-756VF") were mixed in amounts shown in Table 1 relative to 100 parts of polymer A1 contained in the composition, to obtain the coating composition of this example.

[0220] (Example B3)

[0221] In the coating composition of Example A1 prepared in Experimental Example 1, titanium oxide (rutile titanium oxide manufactured by Ishihara Sangyo Co., Ltd., trade name "TIPAQUE CR-95", average particle size 280 nm), calcium carbonate (manufactured by Shiraishi Calcium Kaisha, Ltd., trade name "Softon 3200"), dispersant (manufactured by BYK Co., Ltd., trade name "DISPERBYK-2015"), defoamer (manufactured by Kusunoki Chemical Co., Ltd., trade name "DISPARLON AQ7533") and thickener (urethane associative thickener manufactured by ADEKA Co., Ltd., trade name "ADEKA NOL UH-756VF") were mixed in amounts shown in Table 1 relative to 100 parts of polymer A1 contained in the composition, to obtain the coating composition of this example.

[0222] (Example B4)

[0223] Except that the amounts of calcium carbonate and dispersant are as shown in Table 1, the same procedure as in Example B3 was followed to obtain the coating composition of this example.

[0224] (Examples B5 and B6)

[0225] Instead of the coating composition of Example A1 prepared in Experimental Example 1, the coating composition of Example A3 was used. Otherwise, the same procedures were followed as in Examples B2 and B4 to obtain the coating compositions of each example.

[0226] It should be noted that the solid content of each coating composition, such as B1 to B6, is adjusted to 50% by appropriately adjusting the water content (dilution or concentration).

[0227] <Measurement and Evaluation>

[0228] Viscosity Measurement Based on BH Viscometer

[0229] Viscosities were measured at 30°C using a BH type viscometer with a No. 6 rotor at 2 rpm and 20 rpm. Based on the results, the ratio (Ti value) of the viscosity V1 measured at 2 rpm to the viscosity V2 measured at 20 rpm was calculated. The results are shown in Table 2.

[0230] [Tension Test]

[0231] Similar to Experimental Example 1, test samples were prepared from the coating compositions of each example, and tensile tests were performed to determine the breaking strength and elongation at break. The results are shown in Table 2.

[0232] [Storage Modulus Determination]

[0233] Similar to Experimental Example 1, test samples were prepared from the coating compositions of each example, and viscoelasticity was measured to determine the storage modulus G' at each temperature. The results are shown in Table 2.

[0234] [RSA-Tg]

[0235] The peak temperature of tanδ was determined by the above viscoelasticity measurement, and its temperature is shown as RSA-Tg in Table 2.

[0236] [70℃ peelability]

[0237] On the aforementioned coated steel sheet, the coating compositions of each example were applied using an applicator manufactured by TP Giken Co., Ltd., and dried at 80°C for 3 minutes, thereby forming a 100μm thick film (coating protective coating material) on the coated steel sheet. Next, the coated steel sheet was placed in a constant temperature bath at 70°C, and at this temperature, the peelability of the film when peeled off from the coated steel sheet was evaluated according to the following two criteria.

[0238] 3 points: The film can be peeled off.

[0239] 1 point: Unable to peel off the film (stretches and breaks).

[0240] [Peelability (23℃)]

[0241] Using the coating compositions of each example, a film with a thickness of 100 μm was formed on the coated steel plate in the same manner as evaluated for peelability (70°C) above. The peelability of the film when peeled from the coated steel plate was evaluated at 23°C and 50% RH according to the following two criteria.

[0242] 3 points: The film can be peeled off.

[0243] 1 point: Unable to peel off the film (stretches and breaks).

[0244] [Peelability (-30℃)]

[0245] Using the coating compositions of each example, a film with a thickness of 100 μm was formed on the coated steel plate in the same manner as the above-described peelability (70°C) evaluation. The coated steel plate was placed in a constant temperature bath at -30°C, and at this temperature, the peelability of the film when peeled off from the coated steel plate was evaluated according to the following three criteria.

[0246] 3 points: The film can be peeled off.

[0247] 2 points: The film hardens and becomes difficult to peel off from the coating, but the film can be peeled off.

[0248] 1 point: Unable to peel off the film (stretches and breaks).

[0249] [Anti-mark adhesion]

[0250] The anti-stain adhesion was evaluated using the coating compositions of each example, in the same manner as in Experimental Example 1. The results are shown in Table 2 using the same three criteria as in Experimental Example 1.

[0251] [Table 2]

[0252] Table 2

[0253]

[0254] As shown in Table 2, the self-coated films formed by Examples B1 to B6 all exhibited good peelability and excellent anti-mark adhesion properties.

[0255] The present invention has been described in detail above, but these are merely illustrative and do not limit the scope of the claims. The technology described in the claims includes those derived from various modifications and alterations of the above-described specific examples.

[0256] Industrial availability

[0257] The protective coating material provided by the technology described in this specification is suitable as a protective coating material used in such a way that it is applied to a coated object to protect it from damage, contamination, or other deterioration, and then peeled off from the object after the protective effect has been achieved. The object to be protected can be, for example, a coated metal sheet (e.g., coated steel sheets used in housing materials, building materials, ships, railway vehicles, automobiles, and other transportation equipment) with a coating on its surface (steel sheet, stainless steel sheet, aluminum sheet, etc.), a coated synthetic resin sheet, or molded articles thereof. The aforementioned protective coating material is preferably used, for example, to protect the coating film on an object (an article having a coating film formed by the aforementioned coating treatment, such as an article, such as a metal plate or its molded article, such as a steel plate) that has been coated with a coating of various compositions, such as acrylic coatings, polyester coatings, alkyd coatings, melamine coatings, urethane coatings, acid-epoxy cross-linked coatings, or composites thereof (e.g., acrylic melamine coatings, alkyd melamine coatings).

[0258] Explanation of reference numerals in the attached figures

[0259] 10. Coating materials for film protection

[0260] 20 Protected Objects

[0261] 22 Coating

Claims

1. A protective coating material formed from a liquid coating composition, The coating composition comprises polymer (A) as a base polymer, wherein polymer (A) is a polymer containing acrylic monomer components. The SP value of the polymer (A) is 9.8 (cal / cm). 3 ) 1 / 2 above, The polymer (A) has an acid value of 4.0 mg KOH / g or higher and 20 mg KOH / g or lower. The glass transition temperature of the polymer (A), calculated based on the composition of the monomer components constituting the polymer (A), is below 0°C. The protective coating material has a storage modulus of 0.70 MPa or higher and 1.30 MPa or lower at 70°C.

2. The protective coating material according to claim 1, wherein, The polymer (A) has an acid value of 4.0 mg KOH / g or higher and 15 mg KOH / g or lower.

3. The protective coating material according to claim 1 or 2, wherein, The monomer components constituting the polymer (A) include nitrogen-containing monomers.

4. The protective coating material according to claim 1 or 2, wherein, The glass transition temperature of the polymer (A), calculated based on the composition of the monomer components constituting the polymer (A), is above -20°C.

5. The protective coating material according to claim 1 or 2, wherein, The monomer components constituting the polymer (A) include alkyl (meth)acrylates with alkyl groups having 1 to 3 carbon atoms at the ester terminus, and carboxyl-containing monomers.

6. A coating composition for forming a protective coating material according to any one of claims 1 to 5.

7. The coating composition according to claim 6, wherein the polymer (A) is dispersed in an aqueous emulsion form in an aqueous solvent.

8. A method for coating protection, comprising: Prepare the coating composition according to claim 6 or 7, The coating composition is applied onto the coating film of the protected object, and... The coating composition is dried to form a temporary protective coating material that protects the coating film.

9. The coating protection method according to claim 8, wherein, The coating composition is applied using a slit mold.

Citation Information

Patent Citations

  • Coating for force-feed type roller coating use

    JP2004224874A

  • Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device

    JP2007051271A

  • Coating film protective sheet

    JP2011111552A

  • High frequency module and communication device

    JP2021082914A

  • Movable radiation shield

    JP2022024082A